Validitas Hukum Penggunaan Grafonomi Sebagai Instrumen Pembuktian Dalam Sengketa Bisnis Di Era Digital - Melki T. Tunggati (Faculty of Law, University of Mataram, 2025)
Business disputes involving document and signature forgery are becoming a growing concern in the digital age, where technology makes it easier to manipulate documents electronically. One method used to prove the authenticity of documents is graphology, which analyzes handwriting and signatures to identify forgery. However, the acceptance of graphology as evidence in the Indonesian legal system, especially in digital business disputes, still faces various challenges. This research examines the legal validity of graphology in proving business disputes in the digital era, as well as the associated challenges and solutions. This study employs a normative legal research method focusing on laws and legal concept analysis. The findings indicate that graphology has the potential to be accepted as legitimate evidence in Indonesian courts. Nevertheless, the main challenge is the lack of clear regulations regarding the use of graphology in a digital context, as well as advancements in forgery technology that make graphological analysis increasingly complex. Additionally, the credibility of graphology experts poses a significant issue, particularly concerning the reliability of the methods used in analyzing digital signatures. As a solution, it is recommended that clearer legal standards and standardized procedures regarding the use of graphology in digital documents be developed. Enhancing judges' and lawyers' understanding of graphology is also an important step to improve the acceptance of this method in court. Thus, graphology can become a credible and effective tool in resolving business disputes involving digital documents.